The Effect of Addition of Coral as a Stabilizing Material to the Value of Soil Bearing Capacity - Alfian Adie Chandra (Enrichment : Journal of Management, 2021)
The type of clay that is very sensitive to changes in water content because it can cause changes in the volume of the soil is also known as expansive soil. The comprehensive nature of the soil is identical to the swelling potential of the soil. The potential for development on the soil can also be a problem in the subgrade layer of the road, which will later have a low carrying capacity or CBR value, causing issues on the road. This study aims to increase the carrying capacity of the soil by using coral from Arso 1 and quicklime, using five different grain sizes and using an additional composition of 10% of the original soil weight in each test, in the form of testing the Arterberg limits, standard proctor compaction, and CBR testing. The use of coral helps improve the quality shown to reduce the plastic index, increase soil density and CBR values ​​in the subgrade layer of roads.